Learning path : beginning UX design. Part 2. - Eastment, Amy; Nudelman, Greg; Krause, Will; Mauldin, Joshua; Safari eBooks ([Place of publication not identified] : O'Reilly Media, 2015)
"Today's consumers have sophisticated standards for user experiences. This Learning Path arms you with specific tools for researching and understanding your target audience, devising a strategy for customer engagement, and developing useful product prototypes. Get concepts and techniques for designing amazing user experiences."--Resource description page.
Usability testing and research / Amy Eastment -- Effective sketching for UX design / Greg Nudelman & Will Krause -- Designing and prototyping with Sketch / Joshua Mauldin.
Presenters, Amy Eastment, Greg Nudelman, Will Krause, Joshua Mauldin.
Title and publication information from resource description page (Safari, viewed March 15, 2016).
Keywords: User-centered system design; Human-computer interaction; Product design; Web sites -- Design; Technology -- Design; Graphical user interfaces (Computer systems); Electronic books